Grundtvigs krise i foråret 1844. Forholdet mellem prædiken og salme med henblik på “Sov sødt, Barnlille” - Thodberg, Christian (Grundtvig-Studier, 2005)
Grundtvigs krise i foråret 1844: Forholdet mellem prædiken og salme med henblik pa “Sov sodt barnlille ” [Grundtvig’s crisis in Spring 1844: The Relationship between sermon and hymn with reference to “Sov sodt barnlille ” ( “Sleep sweet, my baby) ”] By Chr. Thodberg In Spring 1844 Gr was struck down by depression associated with an attack of mumps [parotitis epidemica] which in its final phase developed into inflammation of the brain. His handwriting became small and frail. In the period towards Easter, a number of his sermons were taken on in turn by friends and followers, and the illness reached its peak in the weeks following Easter, and elicited an unreasonable criticism from Bishop J. P. Mynster, who accused Gr of dereliction of duty because he had difficulty in keeping up with his services. Gr’s debilitation culminates in a deep spiritual crisis on the Third Sunday after Easter. The words of Jesus, that in “a little while” he will leave the disciples and in “a little while” will see them again (John 16,16) Gr made into his own words: he was going to die and was now being laid in the bosom of God and the congregation and he would first meet again in God’s kingdom. And three days later he took his leave of the congregation in the form of a sermon in which he summed up his Christian endeavours as his last word and testament. On 3 May he set off with the family on a convalescence-visit to various clerical friends, and during this period almost the whole of “Sov sødt, barnlille” was written, verse by verse, in a fascinating process. His sermon of the Third Sunday after Easter had already set the tone and reinforced a particular context in the baptismal ritual which Gr used, namely the transition from the Gospel-reading concerning Jesus and the little children (Mark 10,13-16) and its conclusion (“And he took them up in his arms, put [his] hands upon them, and blessed them”) on the one side, and, on the other side, the priest’s laying on of hands with the Lord’s Prayer - in combination, an expression of consolation in the midst of assailing doubt and fear of death. Within the same period of time, the hymn became known to Gr’s followers and was construed and taken to heart as the most popular of evening hymns.